SPRAY CONE ANGLES GENERATED BY A DUAL CENTRIFUGAL INJECTOR - Vásquez, R. A.; Costa, F. S. (Revista de Engenharia Térmica, 2014)
A dual pressure swirl injector is characterized by two independent concentric chambers which can provide independent rotational levels to a single liquid or two different liquids. This paper compares theoretical, semi-empirical and experimental results concerning the spray cone angles formed by injection of water, ethanol and biodiesel through a dual pressure swirl injector. Data are obtained for injection of the same liquid through the primary and secondary chambers and for injection of ethanol in the primary chamber and biodiesel through the secondary chamber of the injector. Experimental data are obtained using photographic techniques and are analyzed by an image processing software developed in Matlab language.